BUSINESS OPPORTUNITIES AND LOGISTICS DEVELOPMENT IN RELATIONS BETWEEN THE NORTHWEST RUSSIA AND THE VAASA REGION ALONG THE E12 STRAIT WITH FOCUS ON KVARKEN PORTS - Petrova, Oxana (My University, 2016)
The aim of this research is to identify business opportunities in trade between the Northwest Russia and the Vaasa Region with the emphasis on the activities of the Kvarken Ports. It is a unique transport concept as it is managed by two countries Finland and Sweden. Kvarken ports is a part of the E12 strait, it provides ferry connection between Finland and Sweden and therefore plays major role in the whole Vaasa region logistics. The research is concentrated on the analysis of emerging trends in economy which help to identify business opportunities for trade development between the target regions. The study provides unique results showing that several industries are developing despite the crisis. For instance, agricultural, chemical, food production and machinery are experiencing growth. Therefore, it is recommended to focus on cooperation with companies from these sectors. Moreover, main trends in demand of the Nordic countries are studied and matched with the supply possibility of Russian companies. Customers’ attitude toward the trade with the Vaasa region and its logistics services is identified based on the interview conducted with case companies from the Northwest Russia. Within-case and cross-case analyses are performed to interpret the interview results. Russian companies show interest towards the Vaasa region market, but several changes in logistics services provided by Kvarken Ports are required. Therefore, an action plan how to proceed with findings and develop cooperation between the Vaasa region and the Northwest Russia is developed.
Keywords: Business opportunities; logistics development; the Vaasa region; the Northwest Russia; NLC; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|